Flux-boosted coating of idiomorphic CuInS2 crystal layers on Mo-coated glass substrate. Issue 20 (5th May 2016) - Kurihara, Masaaki; Hayashi, Fumitaka; Shimizu, Kosuke; Wagata, Hajime; Hirano, Toshiyuki; Nakajima, Yasuhiro; Nishikiori, Hiromasa; Oishi, Shuji; Domen, Kazunari; Teshima, Katsuya
Abstract : The use of the flux coating method enables the direct fabrication of CuInS2 crystal layers on a Mo-coated glass substrate through the in situ conversion of Cu2 S pre-coated on the substrate to CuInS2 from a chloride-based flux. Abstract : Cu–In–Ga–S–Se (CIGSSe) is a promising light-absorber in thin-film photovoltaic cells, as well as a photocathode for solar H2 production, but the fabrication of layers of CIGSSe crystals on substrates is both time- and cost-intensive. Here, we report the fabrication of CuInS2 crystal layers on various precursor-loaded Mo/soda-lime glass (SLG) substrates using a flux coating method. X-ray diffraction analysis indicated that the main phase was CuInS2, while MoS2 which formed through the sulfurization of the Mo substrate was present as a minor phase. Top-surface field-emission scanning electron microscopy (FE-SEM) images indicated that the CuInS2 crystals were sparsely formed on the bare Mo/SLG, In/Mo/SLG, and Cu/Mo/SLG substrates. In contrast, closely packed CuInS2 crystals were formed on Cu2 S/Mo/SLG. Smaller CuInS2 crystals 0.5–1 μm in size were grown on Cu2 S/Mo/SLG compared to those on other substrates. This sharp difference in crystal population and size could be attributed to the pre-loading effect of the precursors. Cross-sectional FE-SEM analysis with energy-dispersive X-ray spectroscopy mapping revealed the homogenous fabrication of idiomorphic CuInS2 crystals on the partially sulfurized Mo substrate, yielding a CuInS2 /MoS2 /Mo heterostructure amenable to photovoltaic applications. The formation mechanism of this unique heterostructure was discussed based on the experimental results.